1974
DOI: 10.1071/ar9740957
|View full text |Cite
|
Sign up to set email alerts
|

Basal metabolic rate in lambs and young sheep

Abstract: Basal metabolic rate (BMR) was determined in 56 crossbred sheep, up to 10 observations being made on each animal between 1 week of age and 2$ years. The level of feeding was varied amongst the sheep so that there was a wide range in growth rate at each age. BMR was estimated as heat production under standard conditions of fasting. Trends during fasting were studied in four sheep at ages 3 weeks, 2 months and 9 months.The effects on BMR of body weight (or fat-free weight), age, prior growth rate and prior nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 34 publications
3
45
1
1
Order By: Relevance
“…The concept that maintenance energy requirement per unit of body weight is influenced by body composition in cattle and sheep has been widely accepted (Blaxter, 1962;Graham et al, 1974). There is evidence indicating that maintenance energy requirement decreases exponentially with increasing age (Graham et al, 1974), which was later adopted by SCA (1990).…”
Section: Equations Abmentioning
confidence: 97%
“…The concept that maintenance energy requirement per unit of body weight is influenced by body composition in cattle and sheep has been widely accepted (Blaxter, 1962;Graham et al, 1974). There is evidence indicating that maintenance energy requirement decreases exponentially with increasing age (Graham et al, 1974), which was later adopted by SCA (1990).…”
Section: Equations Abmentioning
confidence: 97%
“…The fetal allometric exponent for the V0 ,/dry weight relationship (0.725 ± 0.020) is virtually equal to the 0.71 ± 0.02 exponent in the allometric equation relating basal met abolic rate to fat-free body weight during postnatal growth from birth to weaning in lambs [2]. It is also similar to the 0.75 expo nent in Kleiber's equation which relates basal V02 to body weight among mature mammals o f different species [5].…”
mentioning
confidence: 91%
“…The estimated fasting metabolism was found to be increased with increase in ME intake (Table 2). Several other reports (Graham et al, 1974;Ferrel et al, 1976;Blaxter, 1962Blaxter, , 1989 have shown that fasting heat production decreases with prolonged low levels of feeding.…”
Section: Fasting Metabolism As the Basis For Energy Requirementmentioning
confidence: 99%